Identifikasi Penalaran Kreatif Siswa Madrasah Ibtidaiyah dalam Memecahkan Masalah Bangun Ruang - Pratiwi Viyanti; Musa'adatul Fithriyah; Maftuha Aini Hayatun (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
The reasoning is one of the many skills that must be mastered by students when working on math problems. One type of reasoning in mathematics is creative reasoning. Creative reasoning is classified into Local Creative Reasoning (LCR) and Global Creative Reasoning (GCR). The reasoning is called Local Creative Reasoning (LCR) if, in the problem-solving process, the steps are still memorizing or imitating, and only a small part uses creative reasoning. Meanwhile, the reasoning is called the Global Creative Reasoning (GCR) type if the problem-solving is not based on an algorithm and, as a whole, requires creative reasoning. This research aims to identify the types of creative reasoning of Islamic elementary school students in solving geometrical problems. This study used the descriptive qualitative method. The subjects of this study were fifth-grade students of MI Nurul Ulum Moropelang, consisting of 2 students with high mathematical abilities, 2 students with moderate mathematical abilities, and 2 students with low mathematical abilities. Data was collected through tests of mathematical ability, creative reasoning tests and interviews. The results showed that students who had high mathematical abilities were currently using Local Creative Reasoning (LCR) type creative reasoning. In contrast, those with low mathematical abilities did not use both types of creative reasoning in solving geometrical problems.